2018
DOI: 10.1371/journal.pone.0198140
|View full text |Cite
|
Sign up to set email alerts
|

A panel of correlates predicts vaccine-induced protection of rats against respiratory challenge with virulent Francisella tularensis

Abstract: There are no defined correlates of protection for any intracellular pathogen, including the bacterium Francisella tularensis, which causes tularemia. Evaluating vaccine efficacy against sporadic diseases like tularemia using field trials is problematic, and therefore alternative strategies to test vaccine candidates like the Francisella Live Vaccine Strain (LVS), such as testing in animals and applying correlate measurements, are needed. Recently, we described a promising correlate strategy that predicted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 38 publications
6
38
0
Order By: Relevance
“…In contrast to mice, which are highly susceptible to virulent strains of F. tularensis, rats exhibit essentially similar susceptibility as humans and may therefore serve as a better model than the mouse [7]. In support of the utility of using rat cells in the co-culture model, it has been shown that peripheral blood leukocytes from immunized rats were able to control intra-macrophage growth of LVS in a co-culture assay and, as in the mouse model, it was demonstrated that the in vitro hierarchy of intra-macrophage growth control of LVS exhibited a pattern that directly correlated with the efficacy of the investigated vaccines to protect against challenge with a highly virulent strain in vivo [8]. Importantly, a similar co-culture assay was also developed using human-derived cells and this model successfully separated the efficacy of PBMC from LVS-vaccinated persons from non-vaccinated persons to control intracellular growth of the highly virulent strain SCHU S4 [9].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to mice, which are highly susceptible to virulent strains of F. tularensis, rats exhibit essentially similar susceptibility as humans and may therefore serve as a better model than the mouse [7]. In support of the utility of using rat cells in the co-culture model, it has been shown that peripheral blood leukocytes from immunized rats were able to control intra-macrophage growth of LVS in a co-culture assay and, as in the mouse model, it was demonstrated that the in vitro hierarchy of intra-macrophage growth control of LVS exhibited a pattern that directly correlated with the efficacy of the investigated vaccines to protect against challenge with a highly virulent strain in vivo [8]. Importantly, a similar co-culture assay was also developed using human-derived cells and this model successfully separated the efficacy of PBMC from LVS-vaccinated persons from non-vaccinated persons to control intracellular growth of the highly virulent strain SCHU S4 [9].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of in vitro bacterial growth control depend on CD4 + or CD8 + effector T cell functions, including IFN-γ, TNF-α, and nitric oxide (NO) production, as well as roles for IL-6, T-bet, and IL-12Rβ2; in contrast, B cells, NK cells, and myeloid cells have minimal if any contributions [23][24][25][26][27][28][29] . In mice and rats, this in vitro co-culture system has proved to provide a functional correlate of vaccine-induced protection in vivo [30][31][32][33][34] , supporting its relevance for studies of infection and in vivo mechanisms central to protective immunity. Results indicate that mechanisms identified to date do not account for all bacterial growth control, and thus additional mechanisms by which T cells limit intramacrophage bacterial growth await discovery 24,25,35 .…”
mentioning
confidence: 77%
“…The in vitro co-culture approach was designed to mimic in vivo interactions between macrophages and lymphocytes, which are colocalized within the architecture of lymphoid organs such as spleen and lymph nodes. The www.nature.com/scientificreports/ relevance of this tissue culture model to in vivo infection is supported by its demonstrated value in serving as a functional correlate that predicts in vivo efficacy of Francisella and M. tuberculosis vaccines in both mice and rats 20,24,[30][31][32][33][34] . Further, its application has previously uncovered novel mechanisms by which T cells, the dominant cell type responding to in vivo Francisella infection, control infection in vivo, such as IL-6 utilization and engagement of IL12Rβ2 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Because vaccination with Schu S4ΔaroD induced both responses in mice, this vaccine will serve as a valuable tool in future studies to discriminate the specific protective mechanisms. It is noteworthy that vaccination with Schu S4 aroD induced a functional T cell response as determined in the splenocyte co-culture assay [24,26,46]. This assay perhaps is the best "correlate" of immunity thus far identified because it relies on antigen-specific T cells to produce IFN-γ leading to the activation of macrophages that control bacterial replication and survival by inducing anti-microbial and inflammatory genes.…”
Section: Discussionmentioning
confidence: 99%